Comparison of some methods used for estimation of heritability - Tamer Çağlayan; Şeref İnal (Eurasian Journal of Veterinary Sciences)
The purpose of this study is to compare half-sib correlations, parent-offspring correlations, parent-offspring regression and REML methods for estimating heritability of body weight for dillerent age in Japanese quail. In this investigation, 1647 chicks at 6-weeks old were obtained from 20 male and 100 female quail and used as the animal material. After correcting the body weights (or sex effect, heri t abilities were estimated for each method. Half-sib correlations, parent-offspring correlations, parent-offspring regression and REML methods for the heritabilities were between 0.085-0.954, 0,168-0.442, 0.030-0.387 and 0.210-1.000, respectively. Heritabilities estimated by using REML method were moderate or high. However, heritabilities estimated by other methods were too low, Gradually minimum of heritability estimates and standart errors were in half-sib correlations method, maximum of heritability estimates and standart errors were in REML and pa rent-off spring regression methods.